THE EFFECT OF RISK BASED BANK RATING ON FIRM VALUE - Rahadian, Dadan; Handono, Artiar Anjani (TRIKONOMIKA, 2022)
Bank Indonesia has transforms since 1746 influenced various policies issued by Bank Indonesia, one of which is the policy of assessing the soundness of banks. This policy underwent a change which was originally based on CAMEL, until now it became RBBR. This policy is made to assess the performance of banking institutions which will have an impact on the value of the company. Using panel data regression with a total sample of 15 foreign exchange banks for 5 years of research, this study found that the ratios of RBBR are LDR, PDN, NPL, GCG, ROA, NIM and CAR together have a considerable influence on the value of the company as proxied by Tobin’s Q of 76.61%, capital being a variable has a positive and significant effect on firm value.